Theobromine content in chocolate products: a review - Alifiya, Fhahira; Guntarti, Any (Universitas Ahmad Dahlan, 2021)
Chocolate is one of the foods that exist in Indonesia and one of the foods that are loved by people of all ages because of its sweet taste and it easily melts in the mouth. Theobromine is the main ingredient in chocolate products. This compound belongs to the canteen group which has a stimulant effect, relaxes the bronchial muscles, prevents coughs, reduces asthma symptoms and others. But consumed in excess of Theobromine has a side effect of burning the heart. To ensure that the main content is the main content in chocolate products, it is necessary to analyze the content of theobromine as an identity compound in chocolate. The purpose of this review article is to determine the presence of theobromine content in chocolate products, the amount of theobromine content contained in it and to find out the methods that can be used to determine theobromine content in chocolate. Literature searches were conducted on google scholar, pubmed, science direct, proquest, and springer using the keywords